2019
DOI: 10.1155/2019/9302636
|View full text |Cite
|
Sign up to set email alerts
|

Association Study between BGLAP Gene HindIII Polymorphism and Type 2 Diabetes Mellitus Development in Ukrainian Population

Abstract: Type 2 diabetes mellitus (T2DM) belongs to the diseases with hereditary predisposition, so both environmental and genetic factors contribute to its development. Recent studies have demonstrated that the skeleton realizes systemic regulation of energy metabolism through the secretion of osteocalcin (OCN). Thus, the association analysis between HindIII single nucleotide polymorphism of OCN gene (BGLAP) promoter region and T2DM development in Ukrainian population was carried out. 153 individuals diagnosed with T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…In this study, we continued to study the association between BGLAP rs1800247 SNP and T2DM development among Ukrainians. The lack of studied correlation matches both our previous research [9] and Das et al study, which excluded BGLAP rs1800247 SNP as a T2DM potential risk factor [13].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we continued to study the association between BGLAP rs1800247 SNP and T2DM development among Ukrainians. The lack of studied correlation matches both our previous research [9] and Das et al study, which excluded BGLAP rs1800247 SNP as a T2DM potential risk factor [13].…”
Section: Discussionsupporting
confidence: 89%
“…Polymerase chain reaction-restriction fragment length polymorphism analysis (PCR-RFLP) was used for BGLAP rs1800247-genotyping. Full information about genotyping protocol was presented in our previous research [9].…”
Section: Aimmentioning
confidence: 99%
“…3 , and the detailed information of KEGG pathway and GO terms is listed in Table 3 and Additional file 3 , respectively. The enriched pathways (eg, starch and sucrose metabolism and MAPK signaling pathway) and related genes (eg, IL1B and ENPP1 ) have been reported association with T2DM [ 22 24 ], which indicated that lnc-HIST1H2AG-6 and lnc-AIM1-3 might play a role in T2DM.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The content of COL1 not only reflects the mature state of osteoblasts, but also affects the strength of bone, which serves an important role in all stages of osteoblast differentiation [ 38 ]. Known as bone Y-carboxyglutamate protein, OCN is an important bone matrix protein synthesized and secreted by osteoblasts [ 39 ]. It is a specific non-collagen matrix protein and a characteristic marker protein of osteocytes.…”
Section: Discussionmentioning
confidence: 99%